Ethical Principles Application in the Development of AI Systems: a Systematic Mapping Study - Martins, Helena Cristo; Lana, Cristiane Aparecida; Villela, Maria Lúcia Bento (Anais da Conferência Latino-Americana de Interação Humano-Computador (CLIHC); 2026: Anais da XII Conferência Latino-Americana de Interação Humano-ComputadorDO - 10.5753/clihc.2026.20902, 2026)
The widespread adoption of Artificial Intelligence (AI) in high-stakes domains demands the effective operationalization of ethical principles. This study identifies and classifies solutions that support the integration of ethics across the AI system lifecycle. A Systematic Mapping Study was conducted, analyzing 102 studies (2019–2024) and categorizing artifacts by ethical principles, approach types, and development stages. The results show a predominance of conceptual and procedural artifacts in early lifecycle phases, limited support for later stages, an emphasis on Justice and Explicability, and comparatively low attention to Autonomy, revealing persistent gaps between principles and practice.